Q-soft Translation of Q-soft Subgroups - Rasul Rasuli (Journal of New Theory)
In this study, we introduce the concept Q-soft translations of Q-soft subgroups. Next we investigate the properties of them and we prove that every Q-soft translation of Q-soft subgroup is also Q-soft subgroup. Finally, we consider them under homomorphism and anti-homomorphism of Q-soft subgroups and Q-soft normal subgroups. .